Biofuel Production and Rural Employment in Colombia 2009-2015 (2020)
This paper estimates the effect of the biofuel mixing policy on the Colombian rural employment. To this end, we apply an empirical methodology based on autoregressive vectors –VAR–. This one allows us to estimate the short-run employment elasticity and to simulate its evolution when biofuel or its prices suffer a positive shock. We construct a monthly database that contains production, prices, and employment levels during 2009-2015 in Colombia. Underlying empirical structure and how elasticity can be estimated in vector models will be studied, and finally we analyze biofuel promotion policy and its effects on jobs. The estimated dynamic correlations show that there is no appreciable effect on the employment levels when there are variations in biofuels production and prices levels.